Hadith Studies in the Digital Age - Zainul Hasan; Ahmad Mohammad Tidjani (Taqriri: Journal of Al-Hadith Science Studies, 2025)
The development of digital technology has had a significant impact on various areas of life, including Islamic studies, particularly the study of hadith. Digitization has opened up broader and faster access to hadith sources previously available only in print. Through various digital platforms such as Maktabah Syamilah, Kutub Tis'ah Digital, and the Hadith Encyclopedia, researchers, educators, and the general public can now easily browse and study hadith. This study aims to identify the advantages and challenges of using hadith applications in the digital era and describe the process of verifying sanad and matan (transmitted texts) in a modern context. The results show that digitizing hadith provides ease of access, research efficiency, and the preservation of classical Islamic literature. However, on the other hand, various challenges arise, such as the validity of digital sources, incomplete verification standards, and the potential for the spread of false hadith due to weak scientific control. Therefore, an integrative approach between classical hadith methodology and digital technology is needed to maintain the authenticity of sanad and matan (transmitted texts), and to enable hadith science to continue to develop in line with the demands of the times.